A compact and laser-induced source of ultracold strontium atoms - Hsu, Chung Chuan (Nanyang Technological University, 2021)
Strontium has been progressively viewed as an unmissable source of ultracold atoms, with its widespread popularity gaining traction nowadays in the form of optical lattice clocks for frequency and time standards. However, conventional sources of strontium are usually bulky and elaborate, requiring extensive setups in the form of ovens, Zeeman slower and pre-cooling apparatuses. In light of the limitations, this project proposes an alternative, compact and portable method to produce ultracold strontium with an ablation technique. Strontium solid granules are ablated by a focused 1064nm laser, in which strontium atomic vapor is then emitted and trapped in a 3D Magneto-Optical Trap (MOT) formed by six counter-propagating 461nm laser beams and thirty-two Neodymium-Iron-Boron (NdFeB) permanent magnets. Using a single-pulse ablation power of 23W, we achieved a loading time of 4s and an average lifetime τ of around 4s, which is quite long for further quantum technology applications. This newfound portability opens up the possibility of conducting inertial sensing and precision measurement experiments outdoors, such as in relativistic geodesy and metrology. A transportable source of ultracold strontium also finds potential applications in civilian defence and quantum simulation of physical problems. Lastly, the ablation technique used also opens up laser cooling possibilities to other elements such as Tungsten that normally require high temperature.